2023
DOI: 10.1177/03091333231193844
|View full text |Cite
|
Sign up to set email alerts
|

Go or grow? Feedbacks between moving slopes and shifting plants in high mountain environments

Jana Eichel,
Markus Stoffel,
Sonja Wipf

Abstract: High mountains are climate change hotspots. Quickly rising temperatures trigger vegetation shifts such as upslope migration, possibly threatening mountain biodiversity. At the same time, mountain slopes are becoming increasingly unstable due to degrading permafrost and changing rain and snowfall regimes, which favour slope movements such as rockfall and debris flows. Slope movements can limit plant colonization, while, at the same time, plant colonization can stabilize moving slopes. Thus, we here propose that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 159 publications
(226 reference statements)
0
0
0
Order By: Relevance
“…This high trait diversity offers beneficial effects for slope stabilization (Martin et al, 2010;Ohler et al, 2023;Zhu et al, 2015). At this point, the rates of geomorphic processes already decreased, resulting in reduced allogenic pressure (geomorphic disturbance, Eichel, Stoffel, & Wipf, 2023;Haselberger et al, 2021). This may be a result of autogenic factors, specifically ecosystem engineering (Osterkamp et al, 2012), species facilitation that allows the colonization of new species (Brooker et al, 2008;Corenblit et al, 2015;Wheeler et al, 2015) and an accelerated expansion in plant cover, which can be attributed to a more effective utilization of resources via niche differentiation (Díaz et al, 2007;Ravenek et al, 2014).…”
Section: Phase II (Biogeomorphic)mentioning
confidence: 99%
See 2 more Smart Citations
“…This high trait diversity offers beneficial effects for slope stabilization (Martin et al, 2010;Ohler et al, 2023;Zhu et al, 2015). At this point, the rates of geomorphic processes already decreased, resulting in reduced allogenic pressure (geomorphic disturbance, Eichel, Stoffel, & Wipf, 2023;Haselberger et al, 2021). This may be a result of autogenic factors, specifically ecosystem engineering (Osterkamp et al, 2012), species facilitation that allows the colonization of new species (Brooker et al, 2008;Corenblit et al, 2015;Wheeler et al, 2015) and an accelerated expansion in plant cover, which can be attributed to a more effective utilization of resources via niche differentiation (Díaz et al, 2007;Ravenek et al, 2014).…”
Section: Phase II (Biogeomorphic)mentioning
confidence: 99%
“…Incorporation of a trait-based approach has significant potential for advancing biogeomorphology (Larsen et al, 2020;Viles & Coombes, 2022). Previous studies in glacier forelands addressing the role of geomorphic processes in vegetation development have mainly focused on specific landforms and provided descriptive accounts of functional traits during stages of biogeomorphic succession (for a comprehensive overview, see Eichel, 2019;Eichel, Stoffel, & Wipf, 2023;Miller & Lane, 2018). With traits including clonal growth, burial tolerance, resprouting capacity and mat formation, Dryas octopetala L. has been recognized as an ecosystem engineer on lateral moraine slopes, influencing hillslope processes through sediment trapping, run-off reduction and moisture storage (Eichel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in the village of Schneizlreuth in the Alps of Bavaria, Germany, rockfalls have occurred many times in recent years, posing a massive threat to roads and buildings in the region [14]. In recent years, studies have found that forests growing on mountain slopes have obvious protection and mitigation effects on rockfall disasters [15][16][17][18]. Currently, research on the protective effect of forests against rockfalls has been well verified in the mountainous regions of Europe, and some countries (e.g., Switzerland and France) have formulated afforestation policies to cope with rockfalls, 2 of 20 which have achieved good results [17,19,20].…”
Section: Introductionmentioning
confidence: 99%